Aplikasi Pupuk Vermikompos Terhadap Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea mays sacharrata Sturt) serta Intensitas Serangan Hama Utamanya - Uluputty, Muhammad Riadh (Fakultas Pertanian, Universitas Pattimura, 2024)
The potential for agribusiness growth of sweet corn (Zea mays Sacharata Sturt) is quite high because it is very popular and favored by consumers. The study aimed to determine the effect of the dose of vermicompost fertilizer on the growth and yield of sweet corn. The research was conducted using a randomized block design (RBD) with 3 replications, namely K0 = control, K1 = 50 g/plant, K2 = 100 g/plant, and K3 = 150 g/plant. There were 12 experimental units; each treatment was 6 plants, so the total number of plants was 72. The application of vermicompost can increase the growth and production of sweet corn plants. Based on the study's results, sweet corn's growth and yield were significantly affected by the treatment of vermicompost with a dose of 150 g. It was found that the main pest species that infected this plant were Helicoverpa armigera Hubner, Ostrinia furnacalis, and Oxya sp. It is expected that the results of the study can be used in the future regarding the application of a combination of compost and other biological fertilizers in the field.